Comparative genomic analysis of intracranial germ cell tumors – the preliminary study focused on Sonic Hedgehog signaling pathway - Kuleszo, Dominika; Koczkowska, Magdalena; Lipska-Ziętkiewicz, Beata S.; Grajkowska, Wiesława; Adamkiewicz-Drożyńska, Elżbieta; Dembowska-Bagińska, Bożenna; Ciołkowski, Maciej; Iżycka-Świeszewska, Ewa (Contemporary Oncology/Współczesna Onkologia, 2017)
Aim of the study : Examination of copy number changes in a group of intracranial germ cell tumors (GCTs) with particular focus on putative aberrations of the main genes coding SHh pathway proteins. Material and methods : The study was performed on DNA isolated from fresh-frozen tumor tissue samples from eight GCTs, including six intracranial GCTs. The intracranial group consisted of three germinomas, two mature teratomas and one mixed germ cell tumor. Comparative genomic profiling analysis was carried out using microarray-CGH method (Cytosure ISCA UPD 4×180k, OGT). The results were analyzed with Feature Extraction (Agilent Technologies) and Nexus Copy Number (BioDiscovery) softwares. Results and conclusions : Chromosomal aberrations were found in two intracranial germinomas. These tumors were characterized by complex genomic profiles encompassing chromosomes 7, 8, 9, 10, 11, 12, 16, 17 and 19. Common findings were gain at 12p13.33p11.1 of 35 Mbp and gain at 17q11.1q25.3 of 55 Mbp. In one tumor, also SHh (7q36.3), SMO (7q32.1) and GLI3 (7p14.1) copy gains occurred together with 9q21.11q34.3 loss, including PTCH1 , all being elements of SHh signaling pathway. Moreover, both tumors showed various copy gain of genes being ligands, regulators, receptors or target genes of SHh ( MTSS1; PRKACA and FKBP8 ) as well as gain of genes of SHh coopting WNT pathway ( WNT3 , WNT5B , WNT9B in both tumors; WNT16 , WNT2 in pineal lesion). Further studies on larger group are needed to characterize SHh-related gene alterations in intracranial GCTs and for searching genotype-phenotype relations.